Gold(I)‐Catalyzed Nucleophilic Allylation of Azinium Ions with Allylboronates. Issue 22 (25th March 2022) - O'Brien, Luke; Argent, Stephen P.; Ermanis, Kristaps; Lam, Hon Wai
Abstract: Gold(I)‐catalyzed nucleophilic allylations of pyridinium and quinolinium ions with various allyl pinacolboronates are reported. The reactions are completely selective with respect to the site of the azinium ion that is attacked, to give various functionalized 1, 4‐dihydropyridines and 1, 4‐dihydroquinolines. Evidence suggests that the reactions proceed through nucleophilic allylgold(I) intermediates formed by transmetalation from allylboronates. Density functional theory (DFT) calculations provided mechanistic insight. Abstract : Gold(I)‐catalyzed nucleophilic allylations of pyridinium and quinolinium ions with allylboronates are reported. Transmetalation of the allylboronate with gold produces nucleophilic allylgold(I) species that add to the 4‐position of the azinium ion with complete regioselectivity to give functionalized 1, 4‐dihydropyridines and 1, 4‐dihydroquinolines. Density functional theory (DFT) calculations provided mechanistic insight.